Phytochemical and chemotaxonomic study on Piper pleiocarpum Chang ex Tseng. (February 2021) - Su, Xiao-Min; Liang, Qian; Zhang, Xin-Min; Wang, Meng; Wang, Jing; Wen, Zhen-Wei; Liu, Fen; Nie, Ting; Xu, Jiao; Liu, Rui; Xu, Wen-Hui
Abstract: The phytochemical study of Piper pleiocarpum Chang ex Tseng led to the isolation of eighteen compounds (1 –18), including ten lignanoids, galbelgin (1 ), (+) sesamin (2 ), denudatin A (3 ), hancinone (4 ), (7 S, 8 S, 3′ R )-Δ 8' -3, 3′, 4-trimethoxy-3′, 6′-dihydro-6′-oxo-7.0.4′, 8.3′-lignan[(2 S, 3 S, 3a R )-2-(3, 4-dimethoxyphenyl)-3, 3a-dihydro-3a-methoxy-3-methyl-5-(2-propenyl)-6(2H))-benzofuranone] (5 ), (−)-(7 R, 8 R )-machilin D (6 ), (1 R, 2 R )-2-[2-methoxy-4-(( E )-prop-1-enyl)phenoxy]-1-(3, 4-dimethoxyphenyl)propyl acetate (7 ), piperbonin A (8 ), machilin D (9 ), 4-methoxymachilin D (10 ), one amide alkaloid, Δ α, β -dihydropiperine (11 ), six polyoxygenated cyclohexenes, ent -curcuminol F (12 ), uvaribonol E (13 ), ellipeiopsol A (14 ), 1 S, 2 R, 3 R, 4 S -1-ethoxy-2-[(benzoyloxy)methyl]cyclohex-5-ene-2, 3, 4-triol, 3-acetate (15 ), (+)-crotepoxide (16 ), (+)-senediol (17 ), and one benzoate derivative, 2-acetoxybenzyl benzoate (18 ). Their structures were established by spectroscopic data and by comparison with the literature. All the compounds were firstly isolated from P. pleiocarpum, while ten compounds 6 –7, 9 –10, 12 –15, 17 –18 were isolated from the genus Piper and the family Piperaceae for the first time. The chemotaxonomic significance of these compounds was also discussed. The isolation of compounds 6 –7, 9 –10 may be used as chemotaxonomic markers for the genus of Piper . Highlights: Eighteen compounds (1 -18 ) have been firstly isolated from P. pleiocarpum . Ten compounds 6 –7, 9 –10, 12 –15, 17 –18 were firstly isolated from the Piper genus and the family Piperaceae . The chemotaxonomic significance of the isolates was discussed.